Los defensores de indios de la alcaldía mayor de Tabasco (siglo XVI) - Cunill, Caroline (El Colegio de México, A.C., 2012)
During the second half of the sixteenth century, the post of public defender of Indians spread throughout Spanish America, and its missions became more precisely defined, contributing to this effect both the way in which these officers executed their tasks and the publication of legal texts on the matter, conceived by local or metropolitan authorities. By 1591, the protector and defender of Indians or naturales became the essential piece of the recently-created Juzgado General de Indios, an authentic Indian institution that would last until the late colonial period. In order to understand the process, this work analyzes the peculiar evolution of the post of public defender in the Alcaldía Mayor de Tabasco, Gobernación de Yucatán, during the second half of the sixteenth century. Besides revealing the public defenders' identities, status, and wages, the author analyzes their dealings with colonial authorities —the governors of Yucatan, the Royal Audiencias, and the Consejo de Indias–, as well as the Tabaso Indians. All this allows us to understand the central importance this post acquired, not only in the colonial judicial system, but also in the Spanish American government.